(7-2m)(2m+7)-49=m(m-2)

Simple and best practice solution for (7-2m)(2m+7)-49=m(m-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7-2m)(2m+7)-49=m(m-2) equation:


Simplifying
(7 + -2m)(2m + 7) + -49 = m(m + -2)

Reorder the terms:
(7 + -2m)(7 + 2m) + -49 = m(m + -2)

Multiply (7 + -2m) * (7 + 2m)
(7(7 + 2m) + -2m * (7 + 2m)) + -49 = m(m + -2)
((7 * 7 + 2m * 7) + -2m * (7 + 2m)) + -49 = m(m + -2)
((49 + 14m) + -2m * (7 + 2m)) + -49 = m(m + -2)
(49 + 14m + (7 * -2m + 2m * -2m)) + -49 = m(m + -2)
(49 + 14m + (-14m + -4m2)) + -49 = m(m + -2)

Combine like terms: 14m + -14m = 0
(49 + 0 + -4m2) + -49 = m(m + -2)
(49 + -4m2) + -49 = m(m + -2)

Reorder the terms:
49 + -49 + -4m2 = m(m + -2)

Combine like terms: 49 + -49 = 0
0 + -4m2 = m(m + -2)
-4m2 = m(m + -2)

Reorder the terms:
-4m2 = m(-2 + m)
-4m2 = (-2 * m + m * m)
-4m2 = (-2m + m2)

Solving
-4m2 = -2m + m2

Solving for variable 'm'.

Reorder the terms:
2m + -4m2 + -1m2 = -2m + m2 + 2m + -1m2

Combine like terms: -4m2 + -1m2 = -5m2
2m + -5m2 = -2m + m2 + 2m + -1m2

Reorder the terms:
2m + -5m2 = -2m + 2m + m2 + -1m2

Combine like terms: -2m + 2m = 0
2m + -5m2 = 0 + m2 + -1m2
2m + -5m2 = m2 + -1m2

Combine like terms: m2 + -1m2 = 0
2m + -5m2 = 0

Factor out the Greatest Common Factor (GCF), 'm'.
m(2 + -5m) = 0

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(2 + -5m)' equal to zero and attempt to solve: Simplifying 2 + -5m = 0 Solving 2 + -5m = 0 Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -5m = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -5m = 0 + -2 -5m = 0 + -2 Combine like terms: 0 + -2 = -2 -5m = -2 Divide each side by '-5'. m = 0.4 Simplifying m = 0.4

Solution

m = {0, 0.4}

See similar equations:

| 3x^2=3-2x | | 20.553+5.3n=2.3(6.71+3n) | | 2x-2y=23 | | c/6=6/15 | | 6.5(1+.395a)=5.114+4.3a | | 3(3x+2)=-51 | | 5x(x-2)+(-5x-10)= | | 2s-4+2s-19+3s=180 | | 10000x=2.5 | | x^2+12x+27=y | | (-5x-1)2=3 | | 6-3x-6x+3= | | log(0.45)=x | | 25+0.916y=47 | | 25+0.916=47 | | 2t-50+t-29+2t-41=180 | | 8ax-8ax^3=o | | 3(x+2)-4=5 | | 2x+6=y+3 | | 20y+5-3=37 | | 7x(13-5)= | | 14+0.666p=8 | | 75q-90=21 | | (-2x^8+3y^5)(5x^2-5y^6)= | | 6q-15+4=9 | | 5(-2x)-3(4+4x)=0 | | 16+2p-11=15 | | 3y-15+7=4 | | -25.294-.8a=-3.2+2.7(2.7a+5.6) | | 4x+2-2x=9 | | X+30=52-x | | 17=6x+5-3x |

Equations solver categories